Community phylogenetics at the biogeographical scale: cold tolerance, niche conservatism and the structure of North American forests - Hawkins, Bradford A.; Rueda, Marta; Rangel, Thiago F.; Field, Richard; Diniz-Filho, José Alexandre F. (Wiley, 2014)
Aim